Pibid e saberes profissionais: uma análise desse paralelismo sob a ótica de professores em início de carreira - Joi, Stephanie Gonçalves (Universidade Federal de São Carlos, 2021)
The beginning of teaching reveals itself as a phase under construction, permeated by challenges, perspectives and knowledge mobilized by teachers from different sources (historicity, training, experience). It is a transitional phase between initial training and professional practice considered decisive in the teaching career and, therefore, requires a look at research and discussions in the area. In view of this premise and aiming to collaborate with the deepening of research in this field, this study aims to analyze the parallelism between PIBID and professional knowledge, through the eyes of program graduates, contributing to the advancement of research in the field of teacher professionalization. The research outline is focused on the analysis of 15 beginning teachers, graduates of the Pedagogy/UFSCar course and who participated in the program, starting from the question about: what is the perspective of beginning teachers in relation to the professional knowledge that emerges from the actions of the PIBID/UFSCar Pedagogy and do they contribute to the initial training and professional performance of teachers at the beginning of their career? To answer this question, we will use as theoretical contributions and researchers in the area: Bozzini et al. (2018), Cruz et al. (2014), Gatti et al. (2014) and Sousa (2012; 2010) to discuss the historicity and contributions of PIBID; Tardif (1991, 2000, 2002) and Nóvoa (2009; 2019a; 2019b), to discuss teaching knowledge; Oliveira (2011), Mizukami, et al. (2014), for the discussion about teachers starting their careers. A qualitative research was carried out (BOGDAN AND BIKLEN, 1991; LUDKE AND ANDRÉ, 1986), and an exploratory-descriptive study (GIL, 2008; SELLTIZ et al. 1965), developed through questionnaires, with open and closed questions aimed at graduates in Pedagogy – UFSCar, PIBID graduates who participated in the program between 2015 and 2017. Based on these theoretical references, the data were analyzed and organized into five axes of analysis – identity profile of the participants; professional profile of the participants; vision of initial formation; view on participation in PIBID; vision of the experience/beginning of teaching. The results of the study show how the program offers numerous contributions to initial training and insertion into the teaching career, strengthening the parallel between training and profession; the construction of experiential knowledge enhanced by disciplinary and curricular knowledge; reflection on pedagogical practice; the use of different methodologies; the search for different teaching proposals and, consequently, greater security at the beginning of teaching.
Pibid and professional knowledge: an analysis of this parallelism from the perspective of teachers starting their careers
Keywords: PIBID-pedagogia; Saberes; Início da docência; PIBID-pedagogy; Knowledge; Beginning of teaching; CIENCIAS HUMANAS; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM